Reproductive biology of largehead hairtails, Trichiurus lepturus Linnaeus, 1758 in the coastal area of Bantul Regency - Praditha Novianingrum; Djumanto Djumanto; Murwantoko Murwantoko; Eko Setyobudi (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2017)
Largehead hairtail (Trichiurus lepturus) is one commodity fish catches with high production and value in Yogyakarta. The purpose of this research is to analyse reproductive aspects of this fish in coastal area of Bantul Regency. Yogyakar-ta. Those aspects are gonadal maturity level, fecundity, and the length at the first gonadal maturity. Fish samples are taken from the catch of fisherman using gillnet with a mesh sizes of 1.75 and 2 inches in the coastal fishing port of Depok and Samas. The fish collected from January to April 2016 with at least 30 individuals every two weeks. The samples are identified to find their sex and measured to know the length, weight, and gonadal maturity level (TKG). The data analyzed include length distribution, weight, sex ratio, gonadosmoatic index, length at the first gonadal maturity (Lm), fecundity and oocyte diameter. The result shows the fish length varies between 52.8 and 86.2 cm, and weight 115 and 567.2 g. The sex ratio between male and female was 1:0.6. Gonad maturity stage II and III are found every month observation while gonad maturity stage IV found in April. Oocyte diameter in the stage of gonadal ma-turity IV was 0.35-1.02 mm, there were two distribution modus so that the spawning expected partial spawner with fec-undity of 24.601 eggs with range was 12.873-33.534 eggs. Fecundity increased as parent’s body length with equation F= 0,434L2.60. Hairtail expected reaching the length of the first gonadal maturity in 65.55 cm, higher than the average captured, namely 63.4 cm. Abstrak Ikan layur (Trichiurus lepturus) merupakan salah satu komoditas hasil tangkapan ikan di Daerah Istimewa Yogyakarta dengan jumlah produksi dan nilai yang tinggi. Penelitian ini bertujuan untuk mengkaji aspek reproduksi yang meliputi: tingkat kematangan gonad, fekunditas, dan ukuran ikan kali pertama matang gonad layur di perairan pantai Kabupaten Bantul, Daerah Istimewa Yogyakarta. Sampel ikan dikumpulkan dari hasil tangkapan nelayan yang menggunakan jaring insang dengan ukuran mata jaring 1,75 dan 2 inci di Tempat Pelelangan Ikan Depok dan Samas. Pengumpulan sampel ikan dilakukan pada bulan Januari hingga April 2016 setiap dua minggu sekali minimal 30 ekor. Sampel ikan diidentifikasi jenis kelamin, diukur panjang, bobot tubuh, bobot gonad, dan tingkat kematangan gonad (TKG). Data yang dianalisis meliputi sebaran panjang, bobot, nisbah kelamin, indeks kematangan gonad, ukuran ikan kali pertama matang gonad (Lm), fekunditas, dan diameter telur. Hasil pengamatan menunjukkan kisaran panjang ikan 52,8-86,2 cm dan bobot 115-567,2 g, nisbah betina dan jantan sebesar 1 : 0,6. TKG II dan III ditemukan pada setiap bulan pengamat-an sedangkan TKG IV banyak ditemukan pada bulan April. Diameter telur ikan TKG IV berkisar 0,35-1,02 mm, terda-pat dua modus persebaran sehingga pemijahan diduga bertahap dan fekunditas sebanyak 24.601 butir dengan kisaran 12.873-33.534 butir. Fekunditas meningkat seiring panjang tubuh induk dengan persamaan F = 0,434L2,60. Ukuran ikan layur kali pertama matang gonad diperkirakan pada panjang 65,55 cm, lebih panjang daripada ukuran rata-rata tertangkap, yaitu pada 63,4 cm.